Estimation of Malaysia Public Debt Threshold - Kueh, Jerome; Liew, Venus Khim-Sen; Yong, Sze-Wei; Abdullah, Muhammad Asraf (Universiti Sains Malaysia, 2016)
The objective of this study is to examine the implication of the public debt on the economic growth of Malaysia from the perspective of different public debt levels threshold. Threshold Regression method is utilized to identify the public debt threshold from 1991:Q1-2014:Q4 and examine the heterogeneous impacts of the public debt on growth based on certain threshold levels. Empirical results indicate that there is a positive association between the public debt and economic growth when the public debt is below 41% of GDP threshold level. Furthermore, there is a marginal positive impact when the public debt level falls between 41%-53% of GDP threshold levels. However, there is a harmful impact on growth when public debt is above 53% of GDP threshold level. As a result, managing the public debt position and the quality of the debt are important to ensure sustainable economic growth.